Góp phần tìm hiểu tư tưởng dân chủ của Hồ Chí Minh - Lê, Huy Thực (2011)
Tác giả: Lê Huy Thực, CN; Nguyễn Dương Hùng; Nguyễn Thị Hà; Phạm Thu Hiền; Nguyễn Đức Minh -- Từ khóa: Tư tưởng dân chủ; Hồ Chí Minh